Short Communication Effect of Plant Growth Regulators on Production of Vindoline in the Callus of Catharanthus roseus (Biological Sciences - PJSIR, 2007)
. Callus of Catharanthus roseus cultured from leaf explant was proliferated on MS medi um supplemented wi th differen t plant growth regul ators either individua l ly or in combination . One month old call us was used for extraction and quantification of vindol ine in the c.ill u .The hi ghest amount of v i n dol i n e (34.49 µgig) was found i n t h e cal l us sub-cultured on MS medium su ppl emented with 6-ben zyl-am i no pur i ne (Bi\, 5 mg/ I ) whi le 26.82 tg/g v i ndol i ne was observed in callu s produ ced on BA and Ki nctin (K i n) at 1 .0 mg/ I of each i n com bi n ati on . Th e call us produced at different conccntrntion of aux i n s fai led to produ ce si ngly detectable concentration of vindol i nc. ll is concl uded th at cytok in i ns su pplemen ted i n MS medi u m enhance th e prod uction of v i n dolin e in the callus of Cathara111/111s roseus.